عائلیات اسلام اور جدید سوشیالوجی: موافق و متخالف نظریات کا تقابلی مطالعہ: Islamic Family Dynamics and Modern Sociology: A Comparative Study of Converging and Diverging Theories (Al-Qamar, 2025)
The study of family dynamics is central to both Islamic teachings and modern sociological theories, though their approaches and principles often diverge. Islamic family systems are rooted in divine guidance from the Quran and Hadith, emphasizing spirituality, morality, and a clear distribution of roles to foster familial harmony. Conversely, modern sociology often prioritizes individual autonomy, evolving social norms, and the influence of globalization on family structures. This research undertakes a comparative analysis of these two paradigms, identifying areas of convergence, such as the importance of familial unity and social stability, while highlighting points of divergence, including gender roles, intergenerational relationships, and the impact of secularization. The study also examines how modern sociological critiques of traditional family models align or conflict with Islamic principles, offering a balanced evaluation of both frameworks. By integrating classical Islamic scholarship with contemporary sociological discourse, this research provides a nuanced understanding of family dynamics in a rapidly changing world. It aims to present practical insights for bridging the gap between tradition and modernity while ensuring the preservation of family as a cornerstone of society.
Keywords: Islamic family system, modern sociology, comparative analysis, family dynamics, intergenerational relationships, secularization, social stability